Efficacy Study of Early Presumptive Therapy (EPT) for Deep Fungal Infection - Shimazaki, Syuji; Goto, Hideaki; Yoshizawa, Mie; Sakaki, Seiki; Tanaka, Hideharu; Yoshinari, Kiyoshi (Nihon Ishinkin Gakkai zasshi, 2004)
We retrospectively studied the efficacy of early presumptive therapy (EPT). Subjects and Method: Of the critically ill patients admitted from January 1998 to the end of December 2000 to Kyorin University Trauma Burn and Intensive Care Center, 77 cases were diagnosed with suspected deep fungal infection, and EPT was administered. The diagnosis of suspected deep fungal infection was made by definition. EPT (FLCZ 200 to 400mg/day×14 days) was started as soon as the diagnosis was made and continued for two weeks. Its efficacy was retrospectively studied by analyzing the clinical findings, changes in local organisms, and hematological tests. Results: After treatment, 62% of the patients showed improvement in clinical signs of infection, elimination of locally detected fungus, and improvement in the serum diagnosis test. Post-EPT detection levels of the fungus had decreased to 21%. The mean pre-EPT body temperature was 38.7°C±0.6°C, but the mean post-EPT temperature was 36.7°C±0.6°C. The mean level of blood 1, 3-β-D-glucan was 35±13pg/ml at the time the diagnosis was made, but returned to normal levels after treatment had concluded. No patients died as a direct result of the fungal infection. Conclusion: This study of early presumptive therapy in critically ill patients in the emergency and intensive care medicine fields showed the therapy in these, and in high risk patients to be efficacious.